1994
DOI: 10.1002/app.1994.070531311
|View full text |Cite
|
Sign up to set email alerts
|

Sequence determination of vinyl acetate–methyl acrylate copolymers by NMR spectroscopy

Abstract: SYNOPSISVinyl acetate/methyl acrylate ( V/M) copolymers were prepared by free-radical solution polymerization in benzene. Copolymer compositions were obtained from 'H-NMR spectroscopy. Reactivity ratios for the copolymerization of V with M were calculated using the Kelen-Tudos ( K T ) and the nonlinear error in variables (EVM) methods. The reactivity ratios obtained from the K T and EV methods are rv = 0.04 k 0.03 and rM = 7.28 k 2.88 and rv = 0.04 t 0.01 and rM = 7.28 f 0.37, respectively. The microstructure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 13 publications
(2 reference statements)
2
10
0
Order By: Relevance
“…The reactivity ratios for the butyl acrylate/VAc (BA/VAc) and methyl methacrylate/VAc (MMA/VAc) systems are reported to be r BA = 5.939 and r VAc = 0.0262 for BA/VAc and r MMA = 24.025 and r VAc = 0.0261 for MMA/VAc 2. Similar values are reported for methyl acrylate/VAc,3, 4 butyl methacrylate/VAc,5 and ethyl methacrylate/VAc 6. For all of these systems, these differing reactivity ratios imply that the acrylic monomer is preferred for addition to the growing copolymer chain over the VAc monomer.…”
Section: Introductionsupporting
confidence: 56%
“…The reactivity ratios for the butyl acrylate/VAc (BA/VAc) and methyl methacrylate/VAc (MMA/VAc) systems are reported to be r BA = 5.939 and r VAc = 0.0262 for BA/VAc and r MMA = 24.025 and r VAc = 0.0261 for MMA/VAc 2. Similar values are reported for methyl acrylate/VAc,3, 4 butyl methacrylate/VAc,5 and ethyl methacrylate/VAc 6. For all of these systems, these differing reactivity ratios imply that the acrylic monomer is preferred for addition to the growing copolymer chain over the VAc monomer.…”
Section: Introductionsupporting
confidence: 56%
“…The situation developed when the monomer reactivity ratios differ greatly from one another has been extensively described for different systems such as copolymerization of vinyl acetate28–33 and vinylpyrrolidone34–44 with meth(acrylic) monomers.…”
Section: Resultsmentioning
confidence: 99%
“…Microstructure determination of poly(N-acryloylcarbazole), 25 poly(vinylacetate), 26,27 and N-acryloylcarbazole/methyl methacrylate 28 (A/M) copolymers by NMR has already been reported. Brar et al [29][30][31][32] have reported comonomer sequence and cotacticity of vinylacetate copolymers. To the best of our knowledge, the microstructure and thermal studies of N-acryloylcarbazole/vinyl acetate (A/V) copolymers have not been reported so far.…”
Section: Introductionmentioning
confidence: 99%